Analisis Pengaruh Media MP3 terhadap Kemampuan Menghafal Surat Pendek di SMP N 1 Tanah Abang Kabupaten Pali - Dwi Oktaria (IIQ An Nur Yogyakarta, 2022)
This research aimed to analyze the effect of MP3 media on the ability to memorize short letters. This research type was quantitative research using an experimental design. The design used was in the form of Posttest-Only Control Design. In this design, there were two groups that were chosen randomly, namely the group that was given the treatment (experimental) and the group that was not treated (control). The samples used in this research were grade IX students. To obtain data, interview, observation, documentation and test techniques were used. The research results indicated that the application of the media to memorize short letters of class IX students in the subject of Islamic Education at SMP N 1 Tanah Abang, Pali Regency was included in the low category. The media commonly used was the whiteboard media. The ability to memorize short letters at SMP N 1 Tanah Abang, Pali Regency was high when using MP3 media, and low without using MP3 media. It was evidenced by both the 5% significance level and the 1% significance level. Thus, Ha was accepted and H0 was rejected.